A QTL that confers resistance to Colorado potato beetle (Leptinotarsa decemlineata [Say]) in tetraploid potato populations segregating for leptine - Sagredo, B.; Balbyshev, N.; Lafta, A.; Casper, H.; Lorenzen, J.H. (Springer, 2009)
Genetic resistance to Colorado potato beetle (Leptinotarsa decemlineata [Say]) from Solanum chacoense has been incorporated in the tetraploid potato selection, ND4382-19, which is highly resistant and contains moderate level of foliar leptines. We recently reported using ND4382-19 progeny, population ND5873 (ND4382-19 × Chipeta), to map two genes that segregated as complementary epistatic genes that allow accumulation of leptinidine (Lep) and acetyl-leptinidine (AL) on chromosomes 2 and 8, respectively. We describe here the characterization of a second half-sib population NDG116 (ND4382-19 × N142-72). In this population, solasodine from parent N142-72, which has Solanum berthaultii in its background, was predominant over solanidine-based alkaloids. Concentrations of solanidine, leptinidine, and acetyl-leptinidine were 15-, 5-, and 14-fold lower than in the ND5873 population. Nevertheless, Lep and AL mapped to the same locations on chromosomes 2 and 8 of parent ND4382-19, respectively. The two populations were evaluated for resistance to Leptinotarsa in field assays, and by detached leaf assay for population NDG116. In both families, QTL analysis identified a major QTL from ND4382-19 on the distal end of chromosome 2, close to the Lep locus. The contribution of this QTL to resistance ranged from 11 to 34% for ND5873 at four field sites. Contribution to resistance from the linkage group that contains the gene AL for the accumulation of leptine was not detected. In family NDG116, the same chromosome 2 QTL was detected for field and detached leaf assays, explaining 26 and 12% of the variance for defoliation and larval development, respectively. These data may indicate another resistance mechanism besides leptine in the Leptinotarsa resistance observed in these populations.